2021
DOI: 10.1021/acs.jpclett.1c02611
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Perovskite CsPbBr3 Light Emitting Devices Integrated with GaP Nanowire Arrays in Highly Transparent and Durable Functionalized Silicones

Abstract: The architecture of transparent contacts is of utmost importance for creation of efficient flexible light-emitting devices (LEDs) and other deformable electronic devices. We successfully combined the newly synthesized transparent and durable silicone rubbers and the semiconductor materials with original fabrication methods to design LEDs and demonstrate their significant flexibility. We developed electrodes based on a composite GaP nanowire−phenylethyl-functionalized silicone rubber membrane, improved with sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Therefore, the early reported fully printed FPeLEDs based on CNTs anodes only reached the maximum luminance and EQE of 360 cd•m −2 and 0.14%, respectively, as well as minimum bending radius of 5 mm (Fig. 5(a)) [40] .…”
Section: Low Dimensional Carbon Materialsmentioning
confidence: 93%
“…Therefore, the early reported fully printed FPeLEDs based on CNTs anodes only reached the maximum luminance and EQE of 360 cd•m −2 and 0.14%, respectively, as well as minimum bending radius of 5 mm (Fig. 5(a)) [40] .…”
Section: Low Dimensional Carbon Materialsmentioning
confidence: 93%
“…Despite widespread use, Sylgard 184 has significant drawbacks such as high adhesion to silicon substrates [59]. Thus, it can be challenging for the exfoliation of array of 3-5 µm long GaP NWs grown on Si wafers and optoelectronic device fabrication [56].…”
Section: Transparency Morphology and Adhesionmentioning
confidence: 99%
“…In 2021, it was demonstrated that introducing functional groups into the polysiloxane backbone obtained transparent silicone material with reduced adhesion to the silicon substrate. The introduction of phenylethylene substituents into the polysiloxane backbone reduces adhesion to the silicon substrate [59]. Thus, in [59], the preparation of transparent phenylethylene-functionalized silicone rubbers SSR25 was reported with a reduced adhesion value of 0.55 relative to Sylgard 184.…”
Section: Transparency Morphology and Adhesionmentioning
confidence: 99%
“…Alternatively, highly elastic (flexible), hydrophobic, dielectric, bioinert silicone materials based on polydimethylsiloxane (PDMS) and its modifications are promising for fully flexible device fabrication. 22 However, a conventional PDMS (Sylgard 184) was shown to cause the degradation of the perovskite layer due to the presence of a metal catalyst (platinum complex) used for cross-linking. 23 PDMS also is highly permeable to water vapor.…”
Section: Introductionmentioning
confidence: 99%